Forever freedom : being an anthology in prose and verse from England and America - Wedgwood, Josiah C.; Nevins, Allan (Harmondsworth: Penguin Books Ltd; New York, 1942)
"Selected by Josiah C. Wedgwood and Allan Nevins Bibliotheek Camille Huysmans"